Risk factors for surgical intestinal disorders in VLBW infants: Case–control study. Issue 1 (29th December 2015) - Okuyama, Hiroomi; Ohfuji, Satoko; Hayakawa, Masahiro; Urushihara, Naoto; Yokoi, Akiko; Take, Hiroshi; Shiraishi, Jun; Fujinaga, Hideshi; Ohashi, Kensuke; Minagawa, Kyoko; Misaki, Maiko; Nose, Satoko; et al.
Abstract: Background: Very low‐birthweight (VLBW) infants (VLBWI) are at increased risk for surgical intestinal disorders including necrotizing enterocolitis (NEC), focal intestinal perforation (FIP) and meconium‐related ileus (MRI). The aim of this study was to identify disease‐specific risk factors for surgical intestinal disorders in VLBWI. Methods: A retrospective multicenter case–control study was conducted at 11 institutes. We reviewed VLBWI who underwent laparotomy for intestinal disorders including perforation and intractable bowel obstruction. The surgical disorders were classified into four categories (NEC, FIP, MRI, others) based on the macroscopic findings at operation. In order to identify risk factors, two matched controls for each subject were chosen based on gestational age and birthweight. OR and 95%CI were calculated using a conditional logistic regression model and a multivariate model. Results: A total of 150 cases (NEC, n = 44; FIP, n = 47; MRI, n = 42; others, n = 17) and 293 controls were identified. The cases and controls were similar in terms of gestational age and birthweight (cases/controls, 26.7 ± 2.5/26.5 ± 2.6 weeks; 790 ± 256/795 ± 257 g). On multivariate modeling, disease‐specific risk factors were as follows: female (OR, 0.23; 95%CI: 0.06–0.89), respiratory distress syndrome (OR, 35.7; 95%CI: 2.48–514) and patent ductus arteriosus (OR, 10.9; 95%CI: 1.51–79.3) for NEC; outborn delivery (OR, 5.47; 95%CI: 1.48–20.2) for FIP; and twin pregnancy (OR, 4.25; 95%CI: 1.06–17.1), PROM (OR, 6.85; 95%CI: 1.33–35.4) and maternal steroid (OR, 0.23; 95%CI: 0.07–0.79) for MRI. Conclusions: Different risk factors were identified for NEC, FIP and MRI, suggesting that each disease has a different etiology, and that different strategies are required to prevent these diseases.